Albumin-templated platinum (II) sulfide nanodots for size-dependent cancer theranostics. (1st January 2023) - Li, Ming; Wang, Yuan; Li, Ting; Zhang, Juan; Wang, Xue; Luo, Jie; You, Meng; Yang, Tao; Deng, Yibin; Yang, Hong; Ke, Hengte
Abstract: Transition-metal chalcogenides, such as noble metal chalcogenides, hold tremendous potential as efficient agents for photo-induced cancer theranostics due to their unique physicochemical properties. However, a critical bottleneck still lies in exploring simple and controllable methods to synthesize noble metal chalcogenides especially PtS for in vivo photo-induced cancer imaging and simultaneous therapy. Herein, we proposed the albumin-templated synthesis of size-controllable platinum (II) sulfide nanodots (PtS-NDs) for multimodal cancer imaging and potent photothermal therapy. PtS-NDs were precisely synthesized with a tunable size ranging from 2.1 nm to 4.5 nm through a thermodynamically controlled growth inside albumin nanocages. PtS-NDs yielded significant near-infrared (NIR) absorbance and outstanding photothermal conversion under NIR laser irradiation, as well as effective resistance to photobleaching, thereby generating remarkable in vivo photoacoustic signals and distinct hyperthermia at tumor site. Moreover, these nanodots possessed efficient cellular uptake and tumor targeting capabilities in a size-dependent manner, thus leading to controllable diagnostic and thermo-therapeutic efficacy. Specifically, PtS-NDs with core diameter of 4.5 nm displayed preferable in vivo photoacoustic and CT imaging with high sensitivity, spatially and anatomically enhanced imaging contrast, together with hyperthermia mediated tumor ablation. Thus, the albumin-templated biomimetic synthesis provided an insightful strategy on fabricating theranostic PtS-NDs for potential clinical applications. Statement of significance: Noble metal chalcogenides especially PtS are of particular importance in the field of precise nanomedicine to improve both accuracy of cancer diagnosis and efficiency of tumor treatment. However, the intensively preclinical investigation of PtS was limited due to the lack of simple and controllable synthetic methods. Here, we report an albumin-templated biomineralization synthesis of platinum (II) sulfide nanodots (PtS-NDs). Specifically, albumin-templated biomineralization of PtS-NDs was induced by the electrostatic interactions between albumin and Pt 2+, followed by the nucleation and growth inside the albumin nanocages. The resulting PtS-NDs showed good dispersibility and biosafety, as well as size-dependent photophysical properties and biological behaviors. Therefore, albumin-based biomineralization is a promising and safe strategy to facilely fabricate Pt-based chalcogenide for tumor theranostics. Graphical abstract: Image, graphical abstract